2023
DOI: 10.1101/2023.06.06.543830
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genomes of historical specimens reveal multiple invasions of LTR retrotransposons inDrosophila melanogasterpopulations during the 19thcentury

Almorò Scarpa,
Riccardo Pianezza,
Filip Wierzbicki
et al.

Abstract: Transposable element invasions have a profound impact on the evolution of genomes and phenotype. It is thus an important open question on how often such TE invasions occur. Based on strains sampled at different times, previous work showed that four different TE families invaded D. melanogaster during the 20th century. Here we utilize the genomes of historical specimens to extend this work by another 100 years. We found that the LTR retrotransposons Blood, Opus and 412 spread in D. melanogaster in the 19th cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 81 publications
2
18
0
Order By: Relevance
“…3A). This is consistent with previous works suggesting that the P -element invaded D. melanogaster between 1950 and 1980 [Kidwell, 1983, Anxolabéhère et al, 1985, Bonnivard and Higuet, 1999, Scarpa et al, 2023]. Our data thus suggest that Spoink invaded D. melanogaster after the P -element invasion.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…3A). This is consistent with previous works suggesting that the P -element invaded D. melanogaster between 1950 and 1980 [Kidwell, 1983, Anxolabéhère et al, 1985, Bonnivard and Higuet, 1999, Scarpa et al, 2023]. Our data thus suggest that Spoink invaded D. melanogaster after the P -element invasion.…”
Section: Resultssupporting
confidence: 93%
“…Previous work showed that at least seven TE families invaded D. melanogaster populations during the last two hundred years [Scarpa et al, 2023, Schwarz et al, 2021, Kidwell, 1983]. To explore whether additional, hitherto poorly characterised TEs could have invaded D. melanogaster , we investigated long-read assemblies of recently collected D. melanogaster strains [Rech et al, 2022] using a newly assembled repeat library [Chakraborty et al, 2021].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations